2016
DOI: 10.15537/smj.2016.9.14929
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine bleeding induced by glucocorticoid treatment for pemphigus

Abstract: Glucocorticoids are the first-line treatment option for pemphigus. Moreover, abnormal uterine bleeding (AUB) is a rarely reported side effect of glucocorticoid treatment that usually manifests as abnormal and excessive endometrial bleeding; in fact, AUB can be induced by the systemic or topical application of glucocorticoids. In the present report, we describe the cases of 3 patients with pemphigus who developed AUB following glucocorticoid administration. It is important to note that the administration mode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…High glucocorticoids have been shown to be effective in combination with first-line medication for some bleeding disorders because of their coagulation function [ 27 ]. It has also been demonstrated that in a majority of bleeding disorders, it is difficult to control the use of glucocorticoids as it may also lead to hypercoagulability such as in venous thromboembolism [ 58 ]. Furthermore, using glucocorticoids has been linked to the development of a number of metabolic disorders [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High glucocorticoids have been shown to be effective in combination with first-line medication for some bleeding disorders because of their coagulation function [ 27 ]. It has also been demonstrated that in a majority of bleeding disorders, it is difficult to control the use of glucocorticoids as it may also lead to hypercoagulability such as in venous thromboembolism [ 58 ]. Furthermore, using glucocorticoids has been linked to the development of a number of metabolic disorders [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using glucocorticoids has been linked to the development of a number of metabolic disorders [ 59 ]. In contrast, glucocorticoids have also been known to cause bleeding disorders in the uterus and gastrointestinal tract [ 58 , 60 ]. Our study has demonstrated that prednisolone inhibits platelet activity, pointing to its potential role in hypo-coagulation and contradicting the prevalent notion that glucocorticoids promote coagulation.…”
Section: Discussionmentioning
confidence: 99%